Comparison between the Movement ABC-2 and the Zurich Neuromotor Assessment in Preschool Children. Issue 3 (December 2016) - Kakebeeke, Tanja H.; Knaier, Elisa; Köchli, Sabrina; Chaouch, Aziz; Rousson, Valentin; Kriemler, Susi; Jenni, Oskar G.
An established test instrument for the assessment of motor performance in children between 3 and 16 years is the Movement Assessment Battery for Children – Second Edition (M-ABC-2). The Zurich Neuromotor Assessment (ZNA) is also widely used for the evaluation of children's motor performance but has not been compared with the M-ABC-2 for children below five years for the purpose of convergent validity. Forty-seven children (26 boys, 21 girls) between three and five years of age were assessed using the M-ABC-2 and the ZNA3-5. Rank correlations between scores of different test components were calculated. Only low-to-moderate correlations were observed when separate components of these tests were compared (.31 to .68, p  < .05), especially when involving the associated movements from the ZNA3-5 (−.05 to −.13, p  > .05). However, the correlation between summary scores of the two tests was .77 ( p  < .001), and it increased to .84 when associated movements were excluded, which was comparable in magnitude to the test–retest reliability of the M-ABC-2, supporting convergent validity between the two tests. Although the ZNA3-5 and M-ABC-2 measure different aspects of motor behavior, the two instruments may thus measure essentially the same construct.